The End of Programming: The end of classical computer science is coming, and most of us are dinosaurs waiting for the meteor to hit. - Welsh, Matt (Communications of the ACM, 2023)
The article discusses the decline of classical computer programming due to technological advances in AI systems and the author's belief that such programming is becoming obsolete.